Manual vacuum aspiration in first trimester induced abortion: A randomized comparative prospective studies of 100 cases - Prakash H. Parmar,; Ketan I. Gosai,; Kavita M. Dudhrejia,; Kamal D. Goswami,; Shetal S. Prajapati,; Rushikesh R. Mane, (Universiti Kebangsaan Malaysia, 2015)
Background: Induced abortion is one of the safest procedures for unwanted pregnancies in medical practice. Vacuum aspiration is the preferred method for uterine evacuation before 12 weeks of pregnancy. Objectives: To study the efficacy of manual vacuum aspiration (MVA) in o8 wk versus 8–12 wk of pregnancy. Materials and Methods: A randomized comparative prospective study was performed at the Department of Obstetrics and Gynaecology, P D U Medical College, Rajkot, over a period of January 2012 to June 2013. Totally, 100 subjects were enrolled in the study, which were further divided into two groups (o8 wk and 8–12 wk of pregnancy, 50 in each). MVA was performed in both the groups, and comparison was done in view to evaluate completeness of procedure, requirement of add-on procedure, and complications. Results: Of 50 subjects in each group, perforation was found in two cases in group A and one case in group B. Requirement of oxytocics noted in only one case in group B, whereas incomplete abortion noted in two cases in group A and three in group B. All complications were found statistically insignificant (P = 1) between both the groups. Conclusion: This study focused on the efficacy of MVA in higher weeks of gestations, which was equal in both the groups. Thus, MVA is a safe and an acceptable procedure up to 12 wk of pregnancy.